High-performance work practices and job embeddedness: A comprehensive test - Kiazad, Kohyar; Hom, Peter; Schwarz, Gary; Newman, Alexander; Holtom, Brooks (Journal of vocational behavior, 2024)
Using Conservation of Resources (COR) theory, we developed and tested a theoretical model linking high-performance work practices (HPWPs) to employees' quit intentions and job performance via their occupational, organizational, and job-role embeddedness. We also investigated how family embeddedness (FE) in the organization moderated those indirect relationships, addressing long-neglected family influence on HPWP outcomes. For a broad test of model generalizability, we combined multisource data (n = 1663) from four countries (China, Malaysia, Pakistan, and USA) and established that occupational, organizational, and job-role embeddedness are uniquely important mechanisms translating HPWP effects onto employees' quit intentions and job performance. Crucially, our findings challenge the prevalent view that HPWPs influence staying and performing in uniformly positive ways, as well as the nascent view that FE promotes staying. In fact, we find consistent evidence that HPWPs engender thoughts of leaving by increasing occupational embeddedness and diminish performance contributions by increasing organizational embeddedness. Furthermore, our test provides robust evidence that FE can operate as a “pull-to-leave” factor—either by strengthening positive indirect effects or weakening negative indirect effects of HPWPs on quit intentions. •Work-based job embeddedness constructs differentially explain the effects of high-performance work practices•High-performance work practices can increase employee turnover by increasing occupational embeddedness•High-performance work practices can decrease job performance by increasing organizational embeddedness•Family embeddedness is more likely to strengthen thoughts of leaving rather than staying